CHALLENGES OF ALBANIAN WOMEN IN ACADEMIC CAREERS - Daniela Kalaja; Fatlinda Berisha Tahiri (European Scientific Journal, ESJ, 2015)
Education level is an indicator that speaks about the status of women and girls in society. Statistics data according to INSTAT publication "Women and Men in Albania" and the official data of the Ministry of Education and Sports show that despite the high percentage of female staff in the education system, the allocation of women in decision-making positions follows the traditional pyramidal model: the percentage of women directors does not exceed the figure 30 per cent in any of the levels of education. The dominant percentage of the full-time staff, with the title Professor, is men. During 2009-2010 the proportion male/female full-time professors with the title Professor in higher education system was 2.8: 1. In terms of public higher education there are 11 Rectors and there are no women Rectors, Deans are 32 and only 5 women Deans, 98 Head of departments and only 35 women Head of departments. Although girls comprise the largest number of graduation at all levels of education, and provide an important contribution in the field of education, their social status and economic is very unsatisfactory. The study is focused on exploring the challenges that women and girls face in the Albanian reality in career field and academic achievements. In order to fulfill the purpose and objectives of this research, as well as to address the research question of the study is chosen the qualitative approach. Career and academic achievements remain maledominated areas in Albania. The percentage of women involved in career and academic achievement remains very low, a figure attributed to gender inequality in terms of attendance and benefit from higher levels of education. Academic women and girls perceive themselves as a minority group, in an environment completely dominated by men. The lack of socio-historical background and positive role-models of women participation in academic career is another important aspect in assessing the barriers and challenges faced by Albanian women and girls in the field of career and academic achievements. Marriage, divorce, head of household statutes and roles of caring seem to be factors that prevent women and girls for academic career. These roles and statuses, control their work and career, positioning them always as the second ones. Overview, the difference between work, personal care and leisure time show a big difference between men and women. Another finding of the study highlights the differentiated of appropriate skills acquisition for an academic career. Although both sides have opportunity of involvement and commitment, men attain much faster and perform higher to titles and academic posts.